Reading the Silence: Canadian Library Responses to Racial Injustice - Matthews, Amber (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2021)
This paper presents the findings of a research study on the statements issued by the Canadian library community in the wake of George Floyd’s death in May 2020. The study employed mixed-methods content analysis to (a) identify formal responses between May to August 2020; (b) analyze themes; and, (c) identify commitments for future accountability and research. Ninety-seven organizations were in the study and represent large public and academic libraries along with provincial, national, and professional associations. The results show that one third of the sampled Canadian library community formally responded with an organizational statement and fewer situated their organizations as contributors to systemic racism in Canadian society.